(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
Regeneration of tropical forest species depends largely on successful seedling establishment, which is influenced by soil fertility and nutrient management. Nursery propagation of indigenous tropical tree species is often limited by poor soil fertility and inadequate nutrient availability. This study investigated the growth response of Cola lepidota seedlings to selected organic soil amendments under controlled nursery conditions. The experiment was conducted at the Forestry Nursery of Nnamdi Azikiwe University, Awka, Nigeria, using a Completely Randomized Design (CRD) with four treatments; topsoil (control), topsoil amended with cow dung, poultry manure, and pig manure. Each treatment was replicated sixty (60) times. Growth variables measured include collar diameter (CD), seedling height (HT), and leaf chlorophyll content (LCₜᵣₐₙₛ). Results showed that pig manure significantly enhanced seedling growth, recording the highest mean collar diameter (5.7 mm), height (17.1 cm), and chlorophyll content (3.39). Poultry manure also performed well (CD = 5.4 mm; HT = 16.8 cm), while cow dung recorded the lowest values (CD = 4.7 mm; HT = 12.7 cm). ANOVA revealed significant differences (p < 0.05) for collar diameter (F = 6.36) and height (F = 6.37), but no significant difference for chlorophyll content (F = 1.24; p > 0.05). The findings demonstrate that organic amendments, particularly pig and poultry manure, significantly improve early seedling growth through enhanced nutrient availability and soil conditioning. The study recommends the use of pig manure for optimal nursery performance of Cola lepidota species.